Para‐xylene under extreme conditions: A Raman spectroscopic study. (15th March 2021) - Chaurasia, Shivanand; Rao, Usha; Mohan, Ashutosh
Abstract: Para‐xylene is one of the highly used aromatic compounds in petroleum, chemical, agriculture, aviation, and polymer industries, and hence, it is necessary to study p‐Xylene behavior under extreme conditions (high pressure and high temperature). Here, we report a detailed study on p‐Xylene under nanosecond laser‐driven dynamic compression (up to 4.5 GPa) and shock temperatures (up to 1, 300 K). The experimental observations are compared with previous reported study using hydrostatic compression. A time‐resolved Raman spectroscopy is also done for the estimation of shock velocity in the p‐Xylene sample using the intensity ratio of the Raman modes from the shocked region to that of the whole sample region. The shock velocities for the laser energy on sample at 700 mJ (corresponding pressure 2.5 GPa) deduced by the Raman active modes at 810, 827, and 1204 cm −1 are 3.60 ± 0.46, 3.67 ± 0.17, and 3.78 ±0.09 km/s, respectively. One‐dimensional (1‐D) radiation hydrodynamic simulation is also performed for the validation of experimental results. The shock velocity from the simulation at the same laser energy is 3.51 km/s and is in good agreement with the experimental data. The Gruneisen parameters calculated for various Raman modes such as ν 10 (644 cm −1 ), ν 13 (810 cm −1 ), ν 14 (827 cm −1 ), ν 18 (1, 204 cm −1 ), ν 27 (2, 863 cm −1 ), ν 30 (3, 011 cm −1 ), and ν 31 (3, 053 cm −1 ) are γ i = 0.08959 ± 0.00687, 0.1956 ± 0.03851, 0.19888 ± 0.01417, 0.05477 ± 0.02143, 0.09342 ± 0.0335, 0.00551 ± 0.02472, 0.01942 ± 0.02244, respectively, and are volume independent. Abstract : We report a detailed study on p‐xylene under nanosecond laser‐driven dynamic compression. The experimental observations are compared with the static pressure data using diamond anvil cell. Time‐resolved Raman spectroscopy is used for the estimation of shock velocity using the intensity ratio of the Raman modes from the shocked region to whole sample region and compared with one‐dimensional (1‐D) radiation hydrodynamic simulation and also the effect of the higher pressure reflected shock wave from benzene‐glass interface is also reported.